Implementasi Total Quality Management (TQM) dalam Pengendalian Kualitas pada Proyek Pembangunan Gedung Bertingkat Tinggi di Jakarta - M. Alit Suryawan (Universitas Batanghari Jambi, 2026)
The rapid growth of the construction industry in Jakarta has driven an increasing need for an effective quality control system in high-rise building projects. Project complexity, the involvement of many parties, and the demands for construction efficiency and quality have made the implementation of Total Quality Management (TQM) increasingly relevant. This study aims to examine the implementation of TQM in quality control of high-rise building projects in Jakarta and identify challenges and solutions to its implementation. The study used a qualitative approach with a library research method that analyzed reputable international literature, construction quality standards (SNI, ASTM, BS, ISO), and case studies of high-rise building projects in Indonesia. The results showed that the implementation of TQM is still hampered by a lack of top management commitment, limited competent human resources, and a low understanding of TQM tools such as Statistical Process Control, Quality Circles, and Continuous Improvement. Based on a gap analysis between theory and practice, this study developed an integrated TQM framework that takes into account organizational culture, local regulations, and the conditions of the Indonesian construction market. The study concluded that the implementation of an adaptive and sustainable TQM framework can improve the quality of construction results, reduce rework rates, and increase client satisfaction in high-rise building projects in Jakarta.